Fentanyl Delays the Platelet Inhibition Effects of Oral Ticagrelor: Full Report of the PACIFY Randomized Clinical Trial - Ibrahim, Khalil; Shah, Rohan; Goli, Rakesh R.; Kickler, Thomas S.; Clarke, William A.; Hasan, Rani K.; Blumenthal, Roger S.; Thiemann, David R.; Resar, Jon R.; Schulman, Steven P.; McEvoy, John W. (Thrombosis and Haemostasis, 2018)
Morphine delays oral P2Y12 platelet inhibitor absorption and is associated with adverse outcomes after myocardial infarction. Consequently, many physicians and first responders are now considering fentanyl as an alternative. We conducted a single-centre trial randomizing cardiac patients undergoing coronary angiography to intravenous fentanyl or not. All participants received local anaesthetic and intravenous midazolam. Those requiring percutaneous coronary intervention (PCI) with stenting received 180 mg oral ticagrelor intra-procedurally. The primary outcome was area under the ticagrelor plasma concentration–time curve (AUC0–24 hours). The secondary outcomes were platelet function assessed at 2 hours after loading, measured by P2Y12 reaction units (PRUs) and light transmission platelet aggregometry. Troponin-I was measured post-PCI using a high-sensitivity troponin-I assay (hs-TnI). All participants completed a survey of pain and anxiety. Of the 212 randomized, 70 patients required coronary stenting and were loaded with ticagrelor. Two participants in the no-fentanyl arm crossed over to receive fentanyl for pain. In as-treated analyses, ticagrelor concentrations were higher in the no-fentanyl arm (AUC0–24 hours 70% larger, p = 0.03). Platelets were more inhibited by 2 hours in the no-fentanyl arm (71 vs. 113 by PRU, p = 0.03, and 25% vs. 41% for adenosine diphosphate response by platelet aggregation, p < 0.01). Mean hs-TnI was higher with fentanyl at 2 hours post-PCI (11.9 vs. 7.0 ng/L, p = 0.04) with a rate of enzymatic myocardial infarction of 11% for fentanyl and 0% for no-fentanyl (p = 0.08). No statistical differences in self-reported pain or anxiety were found. In conclusion, fentanyl administration can impair ticagrelor absorption and delay platelet inhibition, resulting in mild excess of myocardial damage. This newly described drug interaction should be recognized by physicians and suggests that the interaction between opioids and oral P2Y12 platelet inhibitors is a drug class effect associated with all opioids.Clinical Trial Registration: https://clinicaltrials.gov/ct2/show/NCT02683707(NCT02683707).
Keywords: fentanyl; ticagrelor; platelet inhibition; percutaneous coronary intervention